2021
DOI: 10.1289/ehp8171
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Effects of Prenatal and Early Life Inorganic and Methylated Arsenic Exposure on Atherosclerotic Plaque Development and Composition in Adult ApoE−/− Mice

Abstract: BACKGROUND: Epidemiologic studies indicate that early life arsenic exposures are linked to an increased risk of cardiovascular diseases. Different oxidation and methylation states of arsenic exist in the environment and are formed in vivo via the action of arsenic (+3 oxidation state) methyltransferase (As3MT). Methylated arsenicals are pro-atherogenic postnatally, but pre-and perinatal effects are unclear. This is particularly important because methylated arsenicals are known to cross the placenta. OBJECTIVES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 76 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…Differences have previously been found in the susceptibility of male and female APOE KO mice to atherosclerosis, with a higher predisposition in females [ 10 , 11 ]. This can also explain why the respective atherosclerotic lesion extents were highly similar in our study and that of Kim et al, despite the markedly different combinations of the sex of the mice used and time of atherogenic diet feeding (6 weeks mild atherogenic diet feeding in female mice versus 12 weeks extreme atherogenic diet feeding in male mice, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Differences have previously been found in the susceptibility of male and female APOE KO mice to atherosclerosis, with a higher predisposition in females [ 10 , 11 ]. This can also explain why the respective atherosclerotic lesion extents were highly similar in our study and that of Kim et al, despite the markedly different combinations of the sex of the mice used and time of atherogenic diet feeding (6 weeks mild atherogenic diet feeding in female mice versus 12 weeks extreme atherogenic diet feeding in male mice, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in the same mouse model used for replication in this work showed that an in utero and early-life arsenic exposure can enhance atherosclerosis later in life in apoE −/− mice. 109 Comparing the DNA methylation data from the livers harvested in that study to the top hits from our population-based study, we observed differential DNA methylation in the genes of interest. The fact that these DMPs and DMRs are validated in a different tissue (blood versus liver) that is equally important to CVD, in particular in the context of cardiometabolic disease, provides supporting evidence of a potential causal relationship between arsenic-induced DNA methylation changes and atherosclerosis.…”
Section: Discussionmentioning
confidence: 80%
“…A recent study conducted in the same mouse model used for replication in this work showed that an in utero and early-life arsenic exposure can enhance atherosclerosis later in life in apoE−/− mice. 113 Comparing the DNA methylation data from the livers harvested in that study to the top hits from our population-based study, we observed differential DNA methylation in the genes of interest. The fact that these DMPs and DMRs are validated in a different tissue (blood vs. liver) that is equally important to CVD, in particular in the context of cardiometabolic disease, provides supporting evidence of a potential causal relationship between arsenic-induced DNA methylation changes and atherosclerosis.…”
Section: Discussionmentioning
confidence: 80%